Realizing a Polite Society on Social Media: ASEAN and EU Perspectives - Sholahuddin Al-Fatih; Abdurrahman Raden Aji Haqqi; Asrul Ibrahim Nur (Faculty of Law, University of Jember, Indonesia, 2022)
The flow of information technology development cannot be contained. Migration from the era of citizens to netizens is an impossible thing to avoid. This study aims to examine the relationship between the development of information technology in the digital era, especially on social media, and the Human Rights perspective. This research uses normative legal research methods to find ideal formulations and boundaries for netizens to become polite people interacting on social media. The results of this study show that Indonesian's right to an opinion on social media is a constitutional right that has been regulated in the 1945 NRI Constitution and the UDHR. However, freedom of speech does not mean that there are no limits. The limitations of freedom of speech on social media are through the limitations of norms, especially norms of politeness and decency, whose values are universal.